Pyridone photoelectrocyclizations to pyridophenanthrenes. Issue 32 (10th August 2017) - Zhao, Xuchen; Rainier, Jon D.
Abstract: This article describes the synthesis of pyridophenanthrenes from the stereoselective electrocyclization and [1, 5]-hydride shift sequences of biphenyl pyridones. The regioselectivity of the reaction of meta -substituted biphenyl substrates depended on the electronic environment of the substituents. That is, substrates having electron-withdrawing substituents underwent a regioselective sequence while electron-donating substituents gave mixtures of products. Graphical abstract: